Drawing lessons from "CRISPR/Cas as a minimal cognitive system": a commentary on Yakura. (June 2019) - Keijzer, Fred
Hidetaka Yakura provides an interesting contribution to the discussion on minimal cognition. He develops the idea that the CRISPR/Cas immune system, as present in many bacteria and archaea, can itself be cast as a minimal cognitive system.